Proyecto de inversión para la implementación de una planta productora de ladrillo con tecnología de punta en el Cantón Celica- Loja - Tinoco Jumbo, Roberth Fernando (2017)
In order to improve the way of brick production, the following "Investment Project for the implementation of a Brick Plant with Tip Technology in the Celtic Canton" is proposed in order to contribute to the growth of the canton with new sources of Employment and seeking the satisfaction of the builder presenting a brick of better quality. Complying with the first objective that was made in the market study to determine the unsatisfied demand in the locality that for which was used the technique of the survey that was applied to the different families of the canton, whose purpose is to verify if it is used The brick for the different constructions and buildings in the canton, in addition to determine the existing supply in the sector was used an interview that was applied to 6 owners of the different factories that exist in the locality to determine the amount of brick that they produce for The commercialization and for the projections of the supply in the same way the owners of the existing factories gave us percentage data of how much the bricks production grew annually. Once obtained the results of the market study, it is evident that the unsatisfied demand of the locality is very small in comparison with the production capacity of the factory, for that reason it is not feasible to implement a brick factory in the canton Celica since The cost of implementation and production are very high. But it is proposed to continue the research by expanding the market to the neighboring cantons such as Alamor, Pindal, 5 Zapotillo, Macara and Paltas in order to finish the investigative studies for the investment project. In this context, the technical study was developed, which determines the ideal place to build the brick factory, the production process that would involve the elaboration of the product, the technical machinery that would be necessary for the production process, the size of the project where It mentions the installed and used capacity, a flow of processes is carried out and finally how the brick production plant will be distributed. Next, the organizational and legal study is developed, which consists of the way in which the factory will be built in the canton of Celica in the province of Loja, which will be as a limited liability company, its legal base according to the Laws that govern our country's statutes, regulations, functional flowcharts for the normal and proper functioning of it. It includes economic financial study, which determines the investment of the project, and budget income fixed and variable costs. Finally, with the results obtained in the investigation it is determined that the project is viable with the expansion of the market to the neighboring cantons.